3, 6-Fluoren[5]arenes: synthesis, structure and complexation with fullerenes C60 and C70. Issue 33 (25th March 2021) - Wang, Jia-Qi; Han, Ying; Chen, Chuan-Feng
Abstract : 3, 6-Fluoren[5]arenes with big and rich-electron cavities were conveniently synthesized, which could form stable 1 : 1 complexes with fullerenes in solution. Abstract : A new class of macrocyclic arenes, 3, 6-fluoren[5]arenes, were conveniently synthesized in good yields by one-step reaction. The 3, 6-fluoren[5]arenes had symmetric pentagon structures with big and rich-electron cavities, which made them form 1 : 1 complexes with fullerenes C60 and C70 . The association constants of the complexes were all greater than 10 5 M −1 .